Practice effect associated with the serial administration of the switch task and its implications in the assessment of sports-related concussion. Issue 9 (20th October 2020) - Sicard, Veronik; Simard, Alexe; Moore, Robert Davis; Ellemberg, Dave
ABSTRACT: In the context of return to play assessment following a sports concussion, athletes may have to complete a cognitive task several times within days. The current longitudinal study aimed to examine the practice effect associated with the serial administration of the switch task. We hypothesized that the practice effect would be the greatest between the first and second assessments and that a plateau would be obtained by the third assessment. Forty healthy university students completed the switch task four times at an interval of 48-hour, with half of them doing version A on all visits (AA group), while the others alternated between A and B every other assessment (AB group). For response accuracy, performance generally improved from V1 to V2, and from V2 to V3 ( ps ≤.001), irrespective of group. For reaction time, a significant interaction of Visit × Group was observed. Specifically, AA group performance improved from V1 to V2, and from V2 to V3, while the AB group only improved from V2 to V3 ( ps ≤.01). Performance improved over the first three assessments and stabilized with no statistically significant change between the third and fourth testing sessions. Although the use of an alternative version has helped reduce the practice effect, it did not help in eliminating it. The current results highlight the need for further examination of the practice effect and its implication in clinical decision-making. Clinicians working in the sports concussion field must take the practice effect into account when they use the switch task for serial testing.